Analisis Nilai Moral dalam Novel Orang-Orang Biasa Karya Andrea Hirata dan Pemanfaatannya sebagai Bahan Ajar Pembelajaran Sastra di SMA - Naufal, Muji Zain; Taminah, Taminah (Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia is known for its beauty and for being a friendly and ethical country. However, today negative events such as student riots, intimidation, corruption, theft, drugs, promiscuous sex, sexual harassment, murder, mutilation cases, and similar events are spreading in the country. Therefore, the author is very interested in providing examples of moral values found in the novel Orang Orang Biasa by Andrea Hirata as reference material for students so that they can broaden their horizons about the morals they should have. This research uses a qualitative approach to analyze the moral values contained in the novel Orang orang Biasa written by Andrea Hirata. Data was collected through a literature study that involved reading and recording relevant information. The results showed that there are three categories of moral values in this novel, namely: 1) individual interaction with himself, 2) individual interaction with the surrounding society, and 3) individual interaction with spiritual aspects. The three moral categories are detailed into 19 moral values, including: (1) self-existence, (2) self-confidence, (3) self-esteem, (4) death, (5) longing, (6) revenge, (7) loneliness, (8) vacillation, (9) perseverance, (10) love for children, (11) affection for parents, (12) affection for others, (13) friendship, (14) loyalty, (15) betrayal, (16) helping, (17) worship, (18) gratitude, and (19) accepting fate. This research produces information that can be utilized in the preparation of Indonesian language learning modules for grade XII students in SMA / SMK on KD 3.9, which is related to understanding the content and use of language in novels.